Therapeutic Potential of Nelumbo nucifera (Sacred Lotus) in CNS Disorders (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Nelumbo nucifera (sacred lotus), locally known as Poddo, has been used as food and traditional remedy in Ayurvedic system in India and Traditional Chinese Medicine for a wide range of diseases. During past two decades, there are numerous scientific studies and general reviews have been published on its phytochemistry and pharmacology. However, in this paper, we aim to make a survey on neuropharmacological effects, as well as psychoactivities, of N. nucifera, identifying the active constituents and their proposed mechanism of actions which has not been systematically documented in the literature. Several online databases, including Google Scholar, PubMed, Web of Science, Science Direct, and Scopus were employed to conduct this survey. Previous studies have demonstrated that N. nucifera has potential neuropharmacological effects in various test systems, including in vivo animal models and in vitro cultured cells or enzymes through various mechanistic pathways, including 5-HT2A receptor blockade, GABAergic system, regulating the NCAM and GAP-43 expression levels, regulating for skolinstimulated cAMP production, and many more. Our survey showed that many alkaloids isolated from N. nucifera demonstrated antidepressant, sedative-hypnotic, anxiolytic, analgesia-potentiating action, anticonvulsant, antipsychotic, and memory enhancer activities. Although many studies have showed potential neurotherapeutic benefits of this plant and many of its constituents, but the focus of research towards clinical trial in human is rather very limited.Dhaka Univ. J. Pharm. Sci. 20(3): 347-358, 2022 (June) Centennial Special Issue